Multilocus Sequence Typing and FlaA Sequencing Reveal the Genetic Stability of Campylobacter jejuni Enrichment during Coculture with Acanthamoeba polyphaga - Griekspoor, Petra (American Society for Microbiology, 2013)
Low concentrations of Campylobacter jejuni cells in environmental samples make them difficult to study with conventional culture methods. Here, we show that enrichment by amoeba cocultures works well with low-concentration samples and that this method can be combined with molecular techniques without loss of genetic specificity.